Probiotics for Prevention of Severe Necrotizing Enterocolitis: Experience of New Zealand Neonatal Intensive Care Units - Meyer, Michael P.; Chow, Sharon S. W.; Alsweiler, Jane; Bourchier, David; Broadbent, Roland; Knight, David; Lynn, Adrienne M.; Patel, Harshad (Frontiers in Pediatrics, 2020)
Introduction: Necrotizing enterocolitis (NEC) affects mainly preterm infants, has a multifactorial aetiology and is associated with intestinal dysbiosis and disordered immunity. Use of probiotics for prophylaxis is beneficial with studies indicating reduction in NEC ? stage 2, late onset sepsis (LOS) and mortality. However, not all studies have shown a reduction, there are questions regarding which probiotic to use, whether infants <1000g benefit and the risk of probiotic sepsis. All neonatal intensive care units in New Zealand (NZ) use probiotics and contribute to an international database (Australian and New Zealand Neonatal Network or ANZNN). Objective: To use ANZNN data to investigate the experience of NZ neonatal units with probiotics for NEC prevention in a setting where the baseline incidence of severe NEC was low, to compare results of 2 commonly used probiotic regimes and report on the extremely low birth weight subgroup. Method: Outcomes before (Pre group 2007-2010) and after (Probiotic group 2013-2015) starting routine probiotics for preterm infants <1500g or <32 weeks were compared. Clinicians reviewed cases to ensure they met database criteria. Five units used Infloran (Bifidobacterium bifidum and Lactobacillus acidophilus) and 1 unit used Lactobacillus GG (LGG) and bovine lactoferrin (bLF). Results: 4529 infants were included and Pre and Probiotic groups were well balanced with regard to gestation, birth weight and gender. The incidence of NEC in the Probiotic group was 1.6% and 2.7% in the pre group (corrected OR 0.62 CI 0.41-0.94). There was one case of probiotic sepsis. There was no significant difference between the Infloran and LGG/bLF combinations in regard to observed NEC rates. Late onset sepsis rates were significantly lower in the Probiotic group (p<0.01). Conclusions: Introduction of probiotics for preterm infants in NZ has been associated with significant reductions in NEC and late onset sepsis.